Role of Anti-MICA Antibodies in Graft Survival of Renal Transplant Recipients of India - Mohit Chowdhry; R. N. Makroo; Mandhata Singh; Manoj Kumar; Yogita Thakur; Vandana Sharma (Journal of Immunology Research)
Introduction. The MIC (MHC class I chain-related) genes are a group of nonclassical MHC genes, located in the MHC class 1 region of chromosome 6. The aim of the present study was to find the prevalence of MHC class 1 chain-related (MICA) alloantibodies in patients undergoing live-related donor renal transplantation and its role in short-term graft survival. The role of blood transfusion in the formation of these antibodies was also studied. Materials and Methods. Pretransplant samples of patients undergoing renal allograft transplantation were tested for anti-MICA antibodies. Association of various demographics, HLA-A + B + DRB1 mismatches, anti-HLA antibody screen, and anti-MICA antibodies was assessed using Pearson’s chi-square test. Results. Out of 646 serum samples, 94 (14.6%) were positive and 552 (85.4%) were negative for anti-MICA antibodies. Patients with anti-MICA antibody had a graft survival 89.3% as compared to 94.7% in patients without anti-MICA antibody (P<0.05). The hazard ratio for all patients was 3.0701 (P<0.05). Out of the 340 patients with no HLA antibodies, the presence of anti-MICA antibodies without any HLA antibodies (n=43) was associated with poor outcome in the patients (hazard ratio of 2.768, P<0.05). The presence of MICA antibodies with HLA antibodies did not decrease the graft survival (hazards ratio of 1.3750, P>0.05). Conclusion. Preformed MICA antibodies independently increase the risk of kidney rejection and therefore recommend that guidelines should be formed for mandatory testing of these antibodies prior to renal transplant.